Social climate profiles in adolescent sports: Associations with enjoyment and intention to continue - Gardner, L. A.; Magee, C. A.; Vella, S. A. (Journal of adolescence, 2016)
This study explored whether adolescent sports participants' perceptions of the social climate fall into distinct profiles, and whether these profiles are related to enjoyment and intention to continue. A Latent Profile Analysis using 313 Australian sports participants (Mage = 13.03 years) revealed four distinct profiles: positive social climate (45.1%), diminished social climate (19.8%), positive coach relationship quality (19.8%), and positive friendship quality (15.3%). Individuals within the positive social climate and the positive coach relationship quality profiles reported relatively higher levels of enjoyment and intention to continue than individuals in the diminished social climate and the positive friendship quality profiles. Indirect path analyses found the social climate profiles were linked with intention to continue through enjoyment. Results highlight the value of investigating multiple dimensions of the social climate and suggest that the coach may be of particular importance in this age group. Findings have implications for understanding youth sports participation and preventing dropout.